The impact of cognitive impairments on the quality of life of patients with multiple sclerosis - Aida Šehanović; Suljo Kunić; Anida Šehanović; Dževdet Smajlović; Emir Tupković; Omer Ibrahimagić (Medicinski glasnik, 2026)
Aim: To assess the impact of cognitive impairments on various domains of quality of life in patients with multiple sclerosis (MS). Methods: This prospective study included 135 MS patients and 50 healthy controls. Participants were divided into three groups: patients with MS for more than one year (n=85), newly diagnosed MS patients (n=50), and healthy individuals (n=50). Neurocognitive assessments included the Mini-Mental State Examination, Wechsler Intelligence Scale, Revised Beta Test, Raven's Coloured Progressive Matrices, Wechsler Memory Scale, Rey-Osterrieth Complex Figure Test, Verbal Fluency Test, Audio-Verbal Learning Test, and the SF-36 Quality of Life Scale. Results: Cognitive impairments were present in 40-60% of MS patients, with memory dysfunctions being the most prominent (30-60%). Longer disease duration was associated with poorer visuospatial, visuoconstructive, and attention-related abilities. Patients also showed reduced logical and working memory. Quality of life was significantly lower in MS groups compared to controls, with a notable correlation between cognitive impairment and decreased MMSE scores. Conclusion: Cognitive impairments in MS patients, particularly those affecting memory, executive functioning, and attention, significantly reduce quality of life. Cognitive testing should be considered essential in assessing disease severity and treatment planning.
Keywords: cognition; Executive function; Neuropsychological tests